Isolation, characterisation and functional properties of pectin from gold kiwifruit (Actinidia chinensis cv. Hort16A) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology at Massey University, Palmerston North, New Zealand - Yuliarti, Oni; Yuliarti, Oni (Massey University, 2011)
This research was concerned with the isolation, physicochemical characterisation and functional properties of pectin from gold kiwifruit cv. Hort16A. The process of extracting pectin from gold kiwifruit was developed by evaluating three different techniques (acid, water and enzyme), four different conditions (time, temperature, puree to solvent ratio and enzyme concentration) and fruit of two different maturities (early-season and main-season fruit). The effects of the extraction techniques and conditions on the physicochemical properties and functional properties of pectin were studied in detail. The effects of the extraction techniques and the fruit maturity on the functional properties of pectin were also investigated. The chemical compositions, physical features and rheological behaviours of the extracted pectins were determined, underlining the importance of these features to the functional properties of gold kiwifruit pectin. The total non-starch polysaccharide composition, sugar composition, protein and ash contents, degree of esterification (DE) and molecular properties (weight-average molecular weight (Mw), polydispersity index and root mean square radius) of pectin are influenced by the extraction techniques, the extraction conditions and the degree of maturity. Pectin from early-harvested fruit (EHF) (less mature fruit) is more difficult to extract than pectin from main-harvested fruit (MHF) (more mature fruit) when using extraction methods that have been developed for MHF. This is probably because the cell wall network of less mature fruit is more compact/dense and the pectin could still be insoluble, whereas the cell wall network of more mature fruit is less tightly bound because of physiological changes during maturation. Purified pectin from EHF is characterised by a lower yield (1.52 versus 3.64% w/w), a higher DE (90 versus 84%), a lower galacturonic acid (GalA) content (40.21 versus 55.50% w/w), more branching chains (a side chain every 47–57 GalA residues versus every 50-97 GalA residues), a higher protein content (25.94 versus 13.82% w/w), a lower Mw (9.7 x 105 versus 2.52 x 106 g/mol) and a higher viscosity than purified pectin from MHF. Overall, the physicochemical properties of gold kiwifruit pectin are consistent with its rheological behaviour. iii Pectins extracted from fruit of different maturities and using different methods have different physicochemical properties. MHF pectin extracted using a water method is characterised by an Mw of 3.75 x 106 g/mol, a GalA content of 51.87% w/w, a degree of branching of 50 and a DE of 84%. MHF pectin extracted using an enzymatic method has a lower Mw (1.65 x 106 g/mol), similar to that of enzyme-extracted EHF pectin (0.21 x 106 g/mol). In contrast, EHF pectin extracted using a water method has low Mw (1.03 x 106 g/mol) and GalA content (42.88%), suggesting that gold kiwifruit pectin with high Mw is recovered from more mature fruit. The rheological properties of the extracted pectin are affected by its Mw and DE. Purified pectin extracted by enzymatic treatment from both EHF and MHF exhibits the lowest viscosity and Mw. Purified EHF pectin obtained by water treatment exhibits a higher viscosity even though the pectin is characterised by a lower Mw (1.03 x 106 g/mol) with a higher DE (90%) compared to acid-extracted EHF pectin (a higher Mw: 1.66 x 106 g/mol and lower DE: 88%). This is because of low electrostatic repulsion of high DE pectin, which reduces intra- and/or intermolecular distances, resulting in greater molecular association, and the greater degree of branching, which leads to more chain-chain associations, therefore exhibits higher viscosity. A similar trend is observed for MHF pectin. Water-extracted MHF pectin, with a high Mw (3.75 x 106 g/mol) and a low DE (84%), exhibits a lower viscosity than EHF pectin (a low Mw but a high DE, i.e. 90%). The viscoelastic properties of the pectin are consistent with its physical properties. Gold kiwifruit pomace, a by-product from gold kiwifruit juice manufacture, may be a new source of pectin. The physicochemical properties of pomace pectin are quite different from those of whole fruit pectin. Purified pomace pectin is characterised by a higher GalA content (64–68% w/w) but a lower Mw (6.7–8.4 x 105 g/mol) and exhibits a lower viscosity. In the work on the functional properties of gold kiwifruit pectin, its gelation was investigated and was compared with that of other commercial pectins (apple and citrus). Gold kiwifruit pectin, which is classified as a high methoxyl pectin (HMP), has “weak gel” properties and gels at high temperature. Because of low electrostatic repulsion among the iv pectin chains, the gelation properties are not markedly affected by varying the gelation conditions such as pH and sugar concentration. However, increasing the concentration of pectin leads to an increase in the gel strength. The viscoelasticity of the gel is strongly influenced by the DE; the gel strength increases as the DE decreases, because high charge density (or low DE) pectins have numerous active sites with high probability for hydrogen bonding, and sufficient hydrophobic interactions, thus resulting in more stabilised molecular networks. A common defect in acidified milk drinks (AMDs) is sedimentation caused by protein aggregation. HMP is commonly added to prevent this separation. In this part of the work, the influence of gold kiwifruit pectins (DE 84, 85 and 90%) on the stability of AMDs (10% w/w low heat skim milk powder) was evaluated and was compared with that of pectins from other sources (apple and citrus). The stabilities, in terms of serum separation, amount of adsorbed and non-adsorbed pectin, viscosity and particle size, were compared at different pectin concentrations (0.1–1.0% w/w). High Mw gold kiwifruit pectin (DE 84%) stabilises an AMD at lower concentrations (0.3% w/w) than other commercial HMPs. In addition, HMPs with very low charge density and very low Mw do not have the ability to stabilise AMDs at the pectin concentrations used in this study. These results suggest that Mw has a very important role in stabilising an AMD. In addition, the viscosity effect created by high Mw apparently supports the dispersion of casein–pectin complexes in the drink.
Keywords: Kiwifruit pectin; Pectin extraction; Acidified milk drinks